Correlation Between Patients’ Medication Adherence and Their Psychological Contract with Hospital Pharmacists - Mu X; Yin C; He X; Li H; Gong Y; Wei W; Zhang Y; Tang F (Patient Preference and Adherence, 2020)
Xingrui Mu,1– 3 Chengchen Yin,1– 3 Xing He,1– 3 Hongfang Li,1– 3 Yuansha Gong,4 Weipeng Wei,1– 3 Yan Zhang,1– 3 Fushan Tang1– 3 1Department of Clinical Pharmacy, School of Pharmacy, Zunyi Medical University, Zunyi 563006, People’s Republic of China; 2The Key Laboratory of Clinical Pharmacy in Zunyi City, Zunyi Medical University, Zunyi 563006, People’s Republic of China; 3Key Laboratory of Basic Pharmacology of Ministry of Education and Joint International Research Laboratory of Ethnomedicine of Ministry of Education, Zunyi Medical University, Zunyi 563006, People’s Republic of China; 4School of Nursing, Zunyi Medical University, Zunyi 563006, People’s Republic of ChinaCorrespondence: Fushan TangSchool of Pharmacy, Zunyi Medical University, Zunyi 563006, People’s Republic of ChinaTel +86 851 2864 2337Fax +86 851 2864 2334Email fstang@vip.163.comObjective: To investigate the correlation between patients’ medication adherence and their psychological contract with hospital pharmacists under the background of the pharmacist–patient relationship, providing a reference for improving the pharmacist–patient relationship and the patients’ medication adherence based on the patients’ psychological contract with the hospital pharmacists.Materials and Methods: Some of the patients who received medication dispensing service at the outpatient pharmacies at the First Affiliated Hospital of Zunyi Medical University and the Second Affiliated Hospital of Zunyi Medical University were included and investigated as follows: 320 patients were included through the convenient sampling method for psychological contract and medication adherence questionnaire survey with the self-designed scales for patients’ psychological contract with the hospital pharmacists and their medication adherence. SPSS 17.0 was used for reliability and validity testing, correlation analysis, and multiple linear regression analysis.Results: The average score of the psychological contract was 3.80± 0.59. The average score of the patients’ medication adherence was 2.93± 0.70. The patients’ psychological contract with the pharmacists and its dimensions (the responsibility of competence, the responsibility of service, and the responsibility of humanistic care) were positively correlated with medication adherence (P< 0.05). The results of the multiple linear regression analysis showed that the effect of patients’ psychological contract with the pharmacists on medication adherence was statistically significant (P< 0.05).Conclusion: Outpatients’ psychological contract with the pharmacists is positively correlated with their medication adherence. Maintaining the patients’ psychological contract with the pharmacists may be an effective way to improve medication adherence.Keywords: psychological contract, medication adherence, the relationship between pharmacists and patients